Clinical Evidence for the Benefits of Burosumab Therapy for X-Linked Hypophosphatemia (XLH) and Other Conditions in Adults and Children - Schindeler, Aaron; Biggin, Andrew; Munns, Craig F. (Frontiers in Endocrinology, 2020)
Burosumab (KRN23) is an FGF23 neutralizing antibody that has been the subject of several recent clinical trials principally focused on the treatment of hypophosphatemic rickets in patients with X-linked hypophosphatemia (XLH). Since the first publications in 2014, these trials have demonstrated efficacy with minimal safety concerns in both adult and pediatric cohorts. These studies have used dose-escalation to establish a dosing regimen that is well-tolerated in clinical use. This review summarizes the clinical trial data with respect to burosumab treatment in adults and children as well as noting several clinical trials currently underway. While burosumab appears transformative for the treatment of XLH, long term follow-up studies would be required to allay concerns over the potential for nephrocalcinosis and cardiac calcification. While these do not appear to be problematic in current trials, the effects of chronic or lifelong treatment have yet to be established.